Modification in light absorption cross section of laboratory-generated black carbon-brown carbon particles upon surface reaction and hydration. (September 2015) - Chen, Hui; Hu, Dawei; Wang, Lin; Mellouki, Abdelwahid; Chen, Jianmin
Abstract: Recent reports indicate that the absorption enhancement of black carbon (BC) and brown carbon (BrC) particles is determined by the evolution of morphology and mixing state during the atmospheric processing. In this study, laboratory-generated BC-BrC mixture particles (BC-BrC) were exposed to sulfuric acid, ammonia/triethylamine, and water vapor sequentially to investigate the alteration in light absorption, morphology and mixing state during simulated atmospheric processing. Condensation of sulfuric acid and exposure to ammonia or triethylamine at 5% relative humidity decreased light absorption cross section of BC-BrC by 13%–26%, but subsequent hydration at 85% relative humidity led to an increase by 5%–20%. Our results show that surface reactions and hydration can significantly alter the light absorption cross section of BC-BrC. Our observation suggests that the restructuring of BC-BrC induced by neutralization reactions on the BC-BrC surface was responsible for the reduction in light absorption cross section at low relative humidity. On the other hand, the formation of an aqueous coating through water uptake by the hydrophilic inorganic coating at high relative humidity caused an absorption enhancement. Highlights: Surface reactions and hydration of BC-BrC particles have been simulated. Neutralization between base gases and condensed sulfuric acid restructured BC-BrC. Restructuring of BC-BrC particles caused reduction in light absorption at low RH. Hydrophilic inorganic coating led to hygroscopic growth of internally mixed BC-BrC. Hygroscopic growth of processed BC-BrC particles enhanced light absorption at high RH.